Politeness Indicators in Nigeria Legislative Discourse - Clara Unoalegie Bola Agbara (Ethical Lingua: Journal of Language Teaching and Literature, 2018)
In every human interaction, interlocutors strive to maintain appropriate decorum and politeness in order to avoid undue feeling of not being ‘nice’ or being insensitive to co-participant’s self-esteem or image. This culture of being ‘nice’ is expressed not only through verbal codes, but also through non-verbal cues such as pitch, tone, voice modulation, facial expression and other forms of body language. Nigeria legislative House reflects the uniqueness of Nigeria as a multicultural nation with about two hundred and fifty ethnic groups. Each tribe has a unique way of expressing ‘nice’ (politeness). This paper examines how Nigerian legislators from different ethnic groups acknowledge the self-esteem of other legislators during senate debates. The study used Scollon and Scollon’s politeness principle which states that in every interaction there is a continuous ‘face’ (self-image) negotiation and this ‘face’ which is made up of two aspects - involvement and independent- must be balanced during interactions because ‘face’ is a paradoxical concept. The interest of this study is to identify and to explain how politicians, who though are in opposition, acknowledge the self-esteem of others. Six hansards were sampled from 2009 to 2010, one bill from each quarter of the year. It was discovered that speakers almost always punctuate their contributions to debate with different types of politeness indicators as a means of acknowledging both the involvement and dependent face wants of participants. The politeness indicators often used by senators include address forms which are used not only as vocative (to the presiding senator) but also as designative (for reference to a third person mentioned in the speech), first person plural pronouns, rhetorical (speech) politeness markers and ritualized utterances.